Novel hybrid excited machine with flux barriers in rotor structure. Issue 4 (10th August 2018) - Wardach, Marcin; Palka, Ryszard; Paplicki, Piotr; Bonislawski, Michal
Abstract : Purpose: Permanent magnet (PM) electrical machines are becoming one of the most popular type of the machines used in electrical vehicle drive applications. The main drawback of permanent magnet machines, despite obvious advantages, is associated with the flux control capability, which is limited at high rotor speeds of the machine. This paper aims to present a new arrangement of permanent magnets and flux barriers in the rotor structure to improve the field weakening control of hybrid excited machines. The field weakening characteristics, back-emf waveforms and efficiency maps of this novel machine have been reported. Design/methodology/approach: In the study, finite element analysis was used to perform simulation research. Then, based on the simulation studies, an experimental model was built. The paper also presents selected experimental results. Findings: Obtained results show that the proposed machine topology and novel control strategy can offer an effective flux control method allowing to extend the maximal rotational speed of the machine at constant power range. Practical implications: The proposed solution can be used in electric vehicles drive to extend its torque and speed range. Originality/value: The paper presents original design and results of research on a new solution of a hybrid excited machine with magnetic barriers in a rotor.